A new species of Psammophis (Serpentes: Psammophiidae) from the Turpan Basin in northwest China - Chen, Minli; Liu, Jinlong; Cai, Bo; Li, Jun; Wu, Na; Guo, Xianguang (Zootaxa, 2021)
An adult sand snake specimen was collected during a herpetofaunal survey conducted in the Turpan Basin in northwest China. Phylogenetic analyses revealed that this specimen, along with other snake sloughs and skins collected from different localities in the Turpan Basin formed a clade that is sister to Psammophis lineolatus. This taxon exhibited substantial divergence from its congeners (P. lineolatus and P. condanarus) with uncorrelated p-distances ranging from 11.9 ± 0.9% to 15.8 ± 1.6% for the ND4 gene and from 10.2 ± 0.8% to 13.8 ± 1.1% for the Cytb gene. Given the genetic differences along with morphological differences, we describe the specimen from the Turpan Basin as Psammophis turpanensis sp. nov. We provide detailed morphological descriptions, and compare this specimen with five Asian sand snakes and the Afro-Asian Sand Snake, P. schokari. In addition, we provide brief comments on the biogeography of Psammophis in China.